Praktik Keagamaan Pekerja Seks Komersial dalam Kehidupan Bermasayarakat pada Kawasan Medan Tuntungan Simpang Selayang - Sari, Widya Permita Tika; Ismail, Ismail (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to reveal the religious practices carried out by prostitutes. This study is a qualitative descriptive study. The data collection methods used are interview methods, observation methods and documentation methods. The results of the study show that: First, the choice to enter the world of prostitution is a materialistic demand that must be met, which usually comes from a broken home and as a widow or someone who is responsible as the backbone of the family. Second, for prostitutes, the job is tempting, and can empower families and improve the economy. The results of the study show that being a prostitute does not make them non-religious people. They even realize that the profession they do is a sin, even so they do not blame God for what happened to them. They believe that what they do is due to coercion due to materialistic demands that they must fulfill and hope that God will forgive their actions. Besides that, if viewed from the Dramartugi theory related to the front and back stage of a sex worker, almost all sex workers play a role, when they become sex workers they act according to their profession, namely by dressing up, wearing sexily, speaking gracefully, with the aim of seducing customers while on the other hand, when at home they behave normally like society in general.